Off-pump versus on-pump coronary artery bypass surgery and postoperative pulmonary dysfunction (2004)
Objective: To investigate how off-pump coronary artery bypass grafting (CABG) affects postoperative pulmonary function when compared with on-pump CABG. Design: Prospective clinical study. Setting: University-affiliated teaching hospital. Participants: Adult patients (n = 39) undergoing elective coronary artery bypass surgery with or without cardiopulmonary bypass. Interventions: Two groups of patients were compared: 19 consecutive patients undergoing off-pump CABG surgery and 20 consecutive patients undergoing conventional CABG surgery. Measurements and Main Results: Pulmonary function tests (flow volume loops and lung volumes with plethysmography) were done preoperatively and 72 hours postoperatively. Arterial blood gases and PaO2/FIO 2 were measured at various stages. Sequential chest x-rays were obtained and evaluated for pleural changes, pulmonary edema, and atelectasis. In both groups, PaO2/FIO2 ratios decreased progressively throughout the perioperative period, with no significant differences between the groups at any stage during the study. There was a significant decline in postoperative pulmonary function tests in both groups, but there was no difference between groups at 72 hours postoperatively. No differences were found in the time to extubation, atelectasis scores, or postoperative complications. Conclusions: Off-pump CABG does not confer major protection from postoperative pulmonary dysfunction compared with CABG surgery with CPB. Strategies for minimizing pulmonary impairment after CABG surgery should be directed to factors other than the use of CPB. © 2004 Elsevier Inc. All rights reserved.